Impact of the Temperature of Waste Biomass Py-Rolysis on the Quality of the Obtained Biochar (Agricultural Engineering, 2016)
Combustion and co-combustion of biomass from different sources is one of the most popular technologies applied in Poland. It allows management of numerous industrial, communal and agricultural waste. Organic waste constitutes one of the richest sources of cheap biomass solid fuels since they are very popular. The paper includes an assessment of practical use of biomass waste: hazelnut shell and pistachio nut shell. The impact of pyrolysis temperature (300, 450 and 550°C) of the investigated biomass on the quality of the obtained biochar was determined and the optimal temperature of this process was defined. The quality of the investigated biomass was analysed on account of its use for energy purposes. Numerous advantageous properties of the obtained materials were found out, for instance: low content of ash and a noticeable increase of the calorific value with an increase of the pyrolysis temperature.